Assessing the Presence of Pithomyces chartarum in Pastureland Using IoT Sensors and Remote Sensing - Ávila, Mariana (2024)
This research was funded by PO ACORES 2020 program, grant code ACORES-01-0247-FEDER-000046. Publisher Copyright: © 2024 by the authors.